Antidepressant effects of total iridoids of Valeriana jatamansi via the intestinal flora-blood–brain barrier pathway. (1st January 2021) - Zhang, Li; Wang, Liwen; Huang, Li; Zhao, Yanni; Ding, Hongling; Li, Binglong; Wen, Lingmiao; Xiong, Wei; Liu, Yanjun; Zhang, Tinglan; Zhang, Liudai; Wu, Lanlan; et al.
Abstract: Context: Valeriana jatamansi Jones [syn. V. wallichii DC, (Valerianaceae)] (VJJ) is used to treat depression. Objective: To explore the effects of total iridoids of VJJ extract (TIV) on chronic unpredictable mild stress (CUMS) in mice. Materials and methods: VJJ roots and rhizomes were extracted with 70% ethanol. CUMS rats were treated daily with fluoxetine (2.6 mg/kg, i.g.) or TIV (5.7, 11.4, and 22.8 mg/kg, i.g.) for 14 days. Male Kun Ming mice on normal chow and 0.5% CMC–Na solution were used as a control. Behavioural tests included the tail suspension (TST) and sucrose preference tests (SPT). Evans blue staining was used to evaluate blood–brain barrier (BBB) permeability. Western blotting was used to measure zonula occludens-1 (ZO-1) and occludin expression. 16S rRNA sequencing was used to analyse intestinal flora abundance. Tax4Fun was used to predict KEGG metabolic pathways. Results: TIV treatment reduced TST time (117.35 ± 8.23 or 108.95 ± 6.76 vs. 144.45 ± 10.30 s), increased SPT (55.83 ± 7.24 or 53.12 ± 13.85 vs. 38.98 ± 5.43%), increased the abundance of phylum Firmicutes (86.99 ± 0.03 vs. 60.88 ± 0.19%) and genus Lactobacillus (75.20 ± 0.19 vs. 62.10 ± 0.13%), reduced the abundance of phylum Bacteroidetes (6.69 ± 0.06 or 11.50 ± 0.09 vs. 25.07 ± 0.20%). TIV increased carbohydrate metabolism (14.50 ± 3.00 × 10 −3 or 14.60 ± 2.00 × 10 −3 or 14.90 ± 2.00 × 10 −3 vs.13.80 ± 4.00 × 10 −3 %), replication and repair functions (5.60 ± 1.00 × 10 −3 or 5.60 ± 1.00 × 10 −3 vs. 5.10 ± 4.00 × 10 −3 %), reduced the frequency of infectious disease (1.60 ± 2.00 × 10 −4 or 1.90 ± 5.00 × 10 −4 or 1.80 ± 3.00 × 10 −4 vs. 2.20 ± 7.00 × 10 −3 %), BBB permeability (0.77 ± 0.30 vs. 1.81 ± 0.33 μg/g), and up-regulated the expression of ZO-1 (1.42-fold, 1.60-fold, 1.71-fold) and occludin (1.79-fold, 2.20-fold). Conclusions: TIV may modulate the intestinal flora, thereby inducing the expression of ZO-1 and occludin, protecting the BBB and exerting an antidepressant effect.